Cara Muslim Menyikapi Makna, Konsep, Dan Peran Filsafat Islam - Nizar, Mohammad; Iqbal, Imam (PT. Kreasi Karya Majakata, 2024)
The theme raised in this paper focuses on the attitude needed by a Muslim towards the food, concept, and role of Islamic Philosophy, especially when facing challenges that come from outside (non-Muslims) and from within (Muslims). The attitude in question is very necessary to deal with negative sentiments about misguidance and disbelief in Islamic philosophy and negative sentiments that doubt Islamic philosophy as an original philosophy because of the influence of Greek philosophy in it. In order to develop this attitude, it is necessary to know first the meaning, concept, and role of Islamic philosophy to explain the situation and problems that gave birth to these two negative sentiments. After that, it will be shown how to behave to show that Islamic philosophy is not something forbidden and is not a copy of previous philosophies.